2015
DOI: 10.1155/2015/893594
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endogenous Controls for Analyzing Serum Exosomal miRNA in Patients with Hepatitis B or Hepatocellular Carcinoma

Abstract: Serum exosomal microRNAs (miRNAs) have received considerable attention as potential biomarkers for diagnosing cancer. The canonical technique for measuring miRNA transcript levels is reverse transcription quantitative polymerase chain reaction (RT-qPCR). One prerequisite for validating RT-qPCR data is proper normalization with respect to stably expressed endogenous reference genes. However, genes that meet all of the criteria of a control gene for exosomal miRNAs have not yet been identified. To find out the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 30 publications
5
55
0
2
Order By: Relevance
“…△CT was used to show the differences between target miRNAs and internal reference (small nucleolar RNA, RNU6). The amounts of target miRNAs in EVs were expressed as CT values [29]. …”
Section: Methodsmentioning
confidence: 99%
“…△CT was used to show the differences between target miRNAs and internal reference (small nucleolar RNA, RNU6). The amounts of target miRNAs in EVs were expressed as CT values [29]. …”
Section: Methodsmentioning
confidence: 99%
“…To find out the control gene for exosomal miRNA normalization, Le et al evaluated the expression stability of 11 reference genes in circulating exosomes, and found that the combination of miR-221, miR-191, let-7a, miR-181a, and miR-26a can be an optimal gene reference set for normalizing the expression of liver-specific miRNAs. This combination enhanced the robustness of the relative quantification analyses (82). …”
Section: Relative Data Normalization To Endogenous Reference Genesmentioning
confidence: 98%
“…geNorm and NormFinder were also employed to investigate on a set of reference genes (5S, U6, hsa-let-7a, hsa-miR-103, hsa-miR-16, hsa-miR-181a, hsa-miR-181c, hsa-miR-191, hsa-miR-22, hsa-miR-221, and hsa-miR-26a) to analyze exosome-associated miRNAs in serum of patients with hepatitis B or hepatocellular carcinoma. The two algorithms have identified the combination of hsa-miR-221, hsa-miR-191, hsa-let-7a, hsa-miR-181a, hsa-miR-181c, and hsa-miR-26a as the optimal reference genes to normalize liver-derived miRNAs [99]. In a recent study on fracture riskassociated miRNA, we used miR-425-5p and miR-484 as reference genes according to a priori analysis [21].…”
Section: Normalization On Endogenous Reference Genesmentioning
confidence: 99%